Tinjaun Perbandingan Perlakuan Insentif Pajak Mobil Listrik Berbasis Sustainable Approach dalam Meningkatkan Program Indonesia Net Zero Emission Pada 2060 (Studi Pada Negara ASEAN): Pemanasan Global - Yaumi, Sri; Nataliawati, Rita; Hakim, Mesra Berlyn; Ani, Mistri; Tiyawati, Sulis (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Global warming is a phenomenon that has attracted world attention recently. Electric cars are an environmentally friendly form of future transportation. The government is committed to increasing the attractiveness of electric vehicles, accelerating the transition from fossil energy to electric energy by providing tax incentives for electric cars. This is also done in other ASEAN countries. The aim of this research is to analyze the electric car incentive policy implemented in Indonesia and analyze best practices in policy development which are then reviewed based on comparisons with ASEAN countries. This research uses a qualitative descriptive method. The types of data in this research are primary data and secondary data. The data analysis method used is comparative descriptive analysis. Indonesia, Singapore, Thailand and Malaysia implement different policies to support the adoption of electric vehicles, adjusted to the conditions and priorities of the governments of each country. The electric car tax incentive has had an impact on the adoption of electric cars, even though currently Indonesia has not shown a significant reduction in carbon emissions. Tax incentive policies have the potential to be effective in the long term, especially if supported by infrastructure improvements and synergy between financial incentives and community readiness.